Genetic and Biochemical Studies of Poliovirus cis-Acting Replication Element cre in Relation to VPg Uridylylation - Rieder, Elizabeth (American Society for Microbiology, 2000)
In addition to highly conserved stem-loop structures located in the 5′- and 3′-nontranslated regions, genome replication of picornaviruses requires cis-acting RNA elements located in the coding region (termed cre) (K. L. McKnight and S. M. Lemon, J. Virol. 70:1941–1952, 1996; P. E. Lobert, N. Escriou, J. Ruelle, and T. Michiels, Proc. Natl. Acad. Sci. USA 96:11560–11565, 1999; I. Goodfellow, Y. Chaudhry, A. Richardson, J. Meredith, J. W. Almond, W. Barclay, and D. J. Evans, J. Virol. 74:4590–4600, 2000). cre elements appear to be essential for minus-strand RNA synthesis by an as-yet-unknown mechanism. We have discovered that the cre element of poliovirus (mapping to the 2C coding region of poliovirus type 1; nucleotides 4444 to 4505 in 2C), which is homologous to the cre element of poliovirus type 3, is preferentially used as a template for the in vitro uridylylation of VPg catalyzed by 3D(pol) in a reaction that is greatly stimulated by 3CD(pro) (A. V. Paul, E. Rieder, D. W. Kim, J. H. van Boom, and E. Wimmer, J. Virol. 74:10359–10370, 2000). Here we report a direct correlation between mutations that eliminate, or severely reduce, the in vitro VPg-uridylylation reaction and produce replication phenotypes in vivo. None of the genetic changes significantly influenced translation or polyprotein processing. A substitution mapping to the first A (A4472C) of a conserved AAACA sequence in the loop of PV-cre(2C) eliminated the ability of the cre RNA to serve as template for VPg uridylylation and abolished RNA infectivity. Mutagenesis of the second A (A4473C; AAACA) severely reduced the yield of VPgpUpU and RNA infectivity was restored only after reversion to the wild-type sequence. The effect of substitution of the third A (A4474G; AAACA) was less severe but reduced both VPg uridylylation and virus yield. Disruption of base pairing within the upper stem region of PV-cre(2C) also affected uridylylation of VPg. Virus derived from transcripts containing mutations in the stem was either viable or quasi-infectious.